Myeloma Bone Disease - Roodman, G. David. (Current Clinical Oncology, 2010)
This state-of-the-art book presents the forefront in the science and clinical management of myeloma bone disease. Assembling the work of the world's premier thought leaders, this book begins with sections on clinical presentation, imaging, and biochemical markers and then goes on to discuss radiation, surgical, and medical therapies. Specific chapters are devoted to bisphosphonates and novel therapeutic agents, such as RANKL inhibitors, Wnt signaling inhibitors, and IMiDs. The mechanisms of osteoclast activation and osteoblast suppression in multiple myeloma are also explored. Myeloma Bone Disease is a valuable resource for medical, surgical, and radiation oncologists and cancer researchers.